NEGERI SABA’ DALAM KEPEMIMPINAN RATU BILQIS - Nila Jazilatul Hikmah; Salim Ashar (Ushuly: Jurnal Ilmu Ushuluddin, 2023)
This reseach is an analysis of the exemplary leadership of Queen Bilqis who succeeded in forming the country of Saba’ as a country with good character and systems in all fields. This success, of course, cannot be separated from his leadership. This study uses a library research base with the approach to the letter saba’ verse 15. The findings in this study regarding the history of Queen Bilqis’a leadership and exemplary as a figure who is a  role model for the country of Saba’ which has characteristics and wisdom, democracy, innovation and promotes the interests in a democratic manner.   Keyword: Saba’ Country, Queen Bilqis.   Abstrak: Penelitian ini merupakan analisis tentang keteladanan kepemimpinan Ratu Bilqis yang berhasil membentuk Negeri Saba’ sebagai negeri yang berkarakter dan bersistem baik di segala bidang. Keberhasilan itu tentunya tidak lepas dari kepemimpinannya. Penelitian ini menggunakan basis library research dengan pendekatan surat saba’ ayat 15. Temuan dalam penelitian ini mengenai sejarah tentang kepemimpinan dan keteladanan Ratu Bilqis sebagai sosok yang menjadi suri tauladan bagi Negeri Saba’ yang memiliki karakteristik dan kebijaksanaan, demokrasi, inovasi serta mengedepankan kepentingan rakyat secara demokratis.   Kata Kunci : Negeri Saba’, Ratu Bilqis.